Subacute Sclerosing Panencephalitis in a Toddler: Changing Epidemiological Trends - Roosy Aulakh; Abhimanyu Tiwari (Hindawi Limited, 2013)
Subacute sclerosing panencephalitis (SSPE) is a devastating "slow virus" brain disease resulting from persistent measles virus infection of neurons. The age at presentation is usually 8 to 11 years with onset usually occurring 2-10 years after measles infection. We report a 2-and-half-year-old boy who presented with progressively increasing myoclonic jerks and subtle cognitive decline. He was diagnosed as a case of SSPE based on clinical features, typical electroencephalographic finding, and elevated cerebrospinal fluid/serum measles antibody titers. He had measles 4 months prior to onset of symptoms. This case along with review of recently published reports suggests progressively decreasing latency period between measles infection and onset of symptoms observed in cases with SSPE. Clinical implication would mean investigating for SSPE even in infants or toddlers with compatible clinical features and recent history of measles infection.